16. OUTCOMES OF TRANSORAL ENDOSCOPIC THYROIDECTOMY VESTIBULAR APPROACH AT MILITARY HOSPITAL 175 (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the outcomes of the transoral endoscopic thyroidectomy vestibular approach (TOETVA) at Military Hospital 175.Subjects and Methods: A cross-sectional descriptive study combined with a prospective clinical interventional design without a control group was conducted on 69 patients who underwent TOETVA at Military Hospital 175 from July 2022 to July 2024.Results: The study, conducted on 69 patients, revealed an average age of 46.5 ± 10.8 years, with females accounting for the majority (79.7%). The proportion of patients without postoperative complications was 81.2%. The most common complications were neck swelling (7.3%), temporary hypocalcemia (17.4%), and surgical site infection (4.3%). Total thyroidectomy had a higher complication rate compared to lobectomy (21.7% vs. 13.0%, p
Keywords: Endoscopic thyroidectomy; transoral vestibular approach; hypocalcemia.